ALK-positive lung adenocarcinoma in a patient with rheumatoid arthritis with long-term treatment for organizing pneumonia: A case report. Issue 49 (9th December 2022) - Horie, Kazuhito; Asakura, Takanori; Masuzawa, Keita; Terai, Hideki; Nakayama, Sohei; Suzuki, Yusuke
Abstract : Rationale: Rheumatoid arthritis (RA) causes inflammation in various organs including the lungs. Pulmonary manifestations include inflammation of the pleura, vasculature, airway, and parenchyma, including interstitial lung disease (ILD). RA-organizing pneumonia (OP) is the third most common cause of RA-ILD. Cases of OP coexisting/complicated with lung cancer have been reported. Therefore, lung cancer can represent a diagnostic challenge, especially in patients with underlying pulmonary diseases including OP. Patient concerns: An 81-year-old woman with a 12-year history of RA-OP underwent multiple transbronchial lung biopsies (TBLBs), all of which resulted in no malignant findings. She was treated with prednisolone (PSL) depending on the deteriorated infiltrations. At admission, chest computed tomography (CT) images showed exacerbation of left S8 consolidation on chest CT. Additionally, her RA activity was exacerbated, and PSL dose was increased to 30 mg/day, which resulted in improved dyspnea and consolidation. Accordingly, PSL dose was gradually decreased. However, 6 months later, when PSL dose was 11 mg/d, due to a worsening of consolidation and the joint symptoms of RA, PSL dose was increased to 20 mg/d and tacrolimus 2 mg/d was administered. 3 months after the increase in PSL dose, dyspnea improved and PSL dose was reduced to 15 mg/d; however, she was admitted to our hospital because of low back pain. Diagnosis: Spinal magnetic resonance imaging showed bone metastases in the third and fifth lumbar vertebrae, and lung cancer was suspected as the primary tumor on CT. Interventions: TBLB was performed on the left B8 infiltrate, which showed no evidence of malignancy in the previous TBLB. Outcomes: Pathological examination of TBLB on the left B8 revealed an adenocarcinoma that was positive for anaplastic lymphoma kinase. Lessons: Physicians should be aware of the development of lung cancer in regions with OP, even after a partial response to corticosteroid therapy.